Learning Patient Safety in Academic Settings: A Comparative Study of Finnish and British Nursing Students' Perceptions. Issue 3 (14th April 2015) - Tella, Susanna; Smith, Nancy‐Jane; Partanen, Pirjo; Turunen, Hannele
ABSTRACT Background Globalization of health care demands nursing education programs that equip students with evidence‐based patient safety competences in the global context. Nursing students' entrance into clinical placements requires professional readiness. Thus, evidence‐based learning activities about patient safety must be provided in academic settings prior to students' clinical placements. Aims To explore and compare Finnish and British nursing students' perceptions of learning about patient safety in academic settings to inform nursing educators about designing future education curriculum. Methods A purpose‐designed instrument, Patient Safety in Nursing Education Questionnaire (PaSNEQ) was used to examine the perceptions of Finnish (n = 195) and British (n = 158) nursing students prior to their final year of registration. Data were collected in two Finnish and two English nursing schools in 2012. Logistic regressions were used to analyze the differences. Results British students reported more inclusion (p < .001) of "gaining knowledge, " "training skills, " and "highlighting affirmative attitudes and motivation" related to patient safety in their programs. Both student groups considered patient safety education to be more valuable for their own learning than what their programs had provided. Training patient safety skills in the academic settings were the strongest predictors for differences (odds ratio [OR] = 34.69, 95% confidence interval [CI] 7.39–162.83), along with work experience in the healthcare sector (OR = 3.02, 95% CI 1.39–6.58). Linking Evidence to Action To prepare nursing students for practical work, training related to clear communication, reporting errors, systems‐based approaches, interprofessional teamwork, and use of simulation in academic settings requires comprehensive attention, especially in Finland. Overall, designing patient safety‐affirming nursing curricula in collaboration with students may enhance their positive experiences on teaching and learning about patient safety. An international collaboration between educators could help to develop and harmonize patient safety education and to better prepare nurses for practice in the global context.